Konsep Hadis Mukhtalif dan Metode Penyelesaian di Kalangan Ulama Hadis dan Fiqih - Fidia Fitri Aqidah Maghfirli (Al Hikmah: Jurnal Studi Keislaman, 2022)
This article discusses the concept of Mukhtalif Hadith and the method of settlement among hadith scholars. As the second source of law after the Qur’an, hadith occopuies a very noble position and Allah greatly glorifies muslims. The journy of hadith is so very long that is reaches our hands today, this is proof that Allah always protect the hadith of prophrt until the end of time. In this journey the hadith has gone through various thereats from outside Islam or from within Islam itself, where effortd to falsify hadith have never stopped, but Allah protects throught thick fortresses, namely the hadith scholars and fiqh scholars who always interact with hadith sincerely and sincerely full of love for the Prophet Muhammad. Hadith in the from of words (qauli), and provisions (taqriri) of the Prophet are not all esay to understand, especially for us as end time hadith student where the time is quite far from the Propeth or his companions. Among the hadith that are classified as rather difficult to understand are those which contradict each other or are commonly referred to as mukhtalif hadith. Mukhtalif Hadith is a hadith that outwardly seems contradictory. To resolve contradictions between one hadith and another, it is necessary to use a method in solving hadith. In the science of mukhtalif hadith if there is a hadith that is considered contradictionary, it is carried out using the al-jam’u wa al-taufiq, method, the second is nasakh, then the Tarjih method. In dealing with mukhtlif hadith, hadith scholars have several views. This paper will explore some of the view of hadith scholars regarding mukhtalif hadith.